Inventory systems analysis of perishable products to improve performance - Tay, Yu Ying (2017)
Perishable goods require adequate planning as the lifetime of the goods pose a limit on the lead time and are likely to decay over a period of time. This results in lost sales and will reduce the profit margin for companies supplying them. Therefore, good inventory management is required to measure the optimal ordering quantity and minimum cost associated with it. Inventory management is vital in handling physical stocks, and in the case of perishable goods, need to ensure that the goods supplied are still within its lifetime, to keep up with the service level they provide. This report examines the performance of inventory models for perishable goods, in particular, Newsvendor, Base stock and (Q, r) models. Based on the demands of a case study, the performance measures of the inventory models will include the optimal order quantity and costs involved. It is important to measure the costs involved, as the aim of companies carrying goods to sell is to gain profit. However, without investment, they are not able to acquire goods. Therefore, it is important to know how much is to be invested to know the amount they will stand to gain. Through the measurement with regards to different quantities and service levels, knowledge will be gained to implement a suitable inventory model for the goods.